Knowledge and knowledge systems learning from the wonders of the mind - Geisler, Eliezer, 1942-; IGI eBooks; IGI Global (Hershey, Pa. : IGI Global (701 E. Chocolate Avenue, Hershey, Pennsylvania, 17033, USA), 2008)
"This book explores the process of knowledge formation and how humans generate complex constructs from their sensorial inputs. It also describes how we store and utilize this complex knowledge in organizational and technological systems that allow us to communicate, generate and manage social interactions and functions, providing value-rich content on a cutting-edge issue to researchers, scholars, and practitioners"--Provided by publisher.
Section IV: Applications of Knowledge Systems in Organizations, The Economy, and Society -- 14. From the Garden of Eden to the Knowledge Society -- 15. The Neuronal Model of Knowledge Systems, Data Mining, and the Performance of Organizations -- 16. Scio, Ergo, Omnis: The Knowledge Perspective of Everything -- Epilogue -- Additional Readings -- Glossary -- About the Contributors -- Index.
Glossary (p. 307-311).
Includes bibliographical references (p. 312-341) and index.
Also available in print.
Mode of access: World Wide Web.
Title from PDF t.p. (viewed on June 26, 2010).
Keywords: Knowledge management; Knowledge, Theory of; Knowledge representation (Information theory); Electronic books